2007
DOI: 10.1007/s00167-006-0271-y
|View full text |Cite
|
Sign up to set email alerts
|

The patella and tibial condyle position after combined and after closing wedge high tibial osteotomy

Abstract: High tibial osteotomy changes the patella and tibial condyle position, which makes the subsequent total knee replacement technically demanding. From 1 January 1993 to 31 December 2000, combined osteotomy [After the first osteotomy made 2 cm distally to the joint line, a bone wedge is removed based laterally. Its tip ends at the center of the tibial condyle (half bone wedge). The distal part of the tibia is placed into the valgus position and the half bone wedge is placed into the gap opened medially.] was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 70 publications
(221 reference statements)
0
9
0
Order By: Relevance
“…Four comparative studies showed the patellar height after both OW and CW HTO. 5,10,14,20 A total of 11 studies [2][3][4]9,15,16,[21][22][23][24][25] reported postoperative changes in patellar height or patellofemoral alignment only after OW HTO and five studies [26][27][28][29][30] reported changes only after CW HTO. The measured indexes used for the evaluation of patellar indexes in each study are shown in ►Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Four comparative studies showed the patellar height after both OW and CW HTO. 5,10,14,20 A total of 11 studies [2][3][4]9,15,16,[21][22][23][24][25] reported postoperative changes in patellar height or patellofemoral alignment only after OW HTO and five studies [26][27][28][29][30] reported changes only after CW HTO. The measured indexes used for the evaluation of patellar indexes in each study are shown in ►Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The distance between the tibial tubercle and the joint line does not change after CO and thus the length of patellar tendon does not change significantly. [19,20] Excessive undercorrection, overcorrection and rotational deformity are not uncommon after a failed HTO [14,28] and the HTO inevitably produces some transposition of the tibial condyle with respect to its bony axis. [29] These factors can lead to difficulty in obtaining optimal soft tissue balancing, appropriate alignment and optimal positioning of the tibial component during the subsequent TKA [15,18,30] In our study, similar to Meding et al, [30] the impingement of the peg of the tibial component against the truncated lateral metaphysis did not occour, the tibial component was not medialized or downsized in any case, because the CO does not lead to significant lateral tibial bone loss and to lateral overhang.…”
Section: Discussionmentioning
confidence: 99%
“…We performed CO [19,20] (combination of lateral closing and medial opening wedge osteotomy) in all cases in 1993. We preferred CO if the planned correction was 10º or higher.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations